Anaplasma Phagocytophilum Intragranulocytic Morulae in Aborting Sheep: A Herd Case in Sicily - Giudice, E.; Giannetto, C.; Torina, A.; Gianesella, M. (Transboundary and emerging diseases, 2011)
Summary The present report describes the haematological and serological findings observed in a dairy sheep farm during an aborting outbreak. Fifty ewes divided into two groups were included in the study: group A consisted of 35 healthy ewes and group B consisted of 15 ill subjects. From each ewe, blood samples were collected for microscopic examination and serological assay. After 3 months, all ewes were subjected to microscopic examination, serological and biochemical assay. Morula‐containing granulocytes characteristic of A. phagocytophilum was observed in all animals of group B. Antibodies against A. phagocytophilum were observed in only one animal of group A. Seroconversion was observed after 3 months in five ewes of group A and all animals of group B. Only one subject with negative serology was positive to PCR. Our results confirm the endemicity of sheep tick‐borne fever (TBF) in Sicily and the problem to breeding in an endemic area. We suggest that is necessary to combine the different assays depending on the stage of infection for a correct diagnosis in endemic areas. Periodic evaluation of seroconversion could be helpful to evaluate the progression of TBF in a flock.